Modified Carbon Paste Electrode with Methyl Orange for Voltammetric Determination of Cysteine - Medanti Achwari, Fauziah
Cysteine is an amino acid that can be produced by the body that functions to create antioxidants in the body. Cysteine has been developed as a medicine for several types of diseases such as Alzheimer's, diabetes, and Human Immunodeficiency Virus (HIV). Determination of cysteine can be done using HPLC, GC-MS, spectrophotometry methods. However, measurement using these methods requires a long analysis time and relatively expensive cost. Therefore, the voltammetry method is used which has advantages such as fast analysis time, sensitive, and selective. In this research a cysteine analysis method was developed using carbon paste electrodes modified with a Molecularly Imprinted Polymer (MIP). The modification process was carried out by electropolymerization of methyl orange as a monomer and cysteine as an analyte. Cysteine was measured using a differential pulse voltammetry technique in 0.1 M phosphate bufer pH 7 in the potential range of 0 - 1.2 V with a scan rate of 50 mY I s. The effect of number of electropolymerization cycles, the composition of cysteine and methyl orange, and the pH of the solution was studied to obtain the optimum conditions of measurement. The optimum measurement of cysteine is at I 0 cycles, 1: I composition of methyl orange : cysteine, and pH 7. The reproducibility test gives% RSD of 6.09%. Linear calibration curves were obtained in the concentration range of I 00 !lM -I 000 !lM with a detection limit of 40.22 !lM. Determination of cysteine in medicine samples by the addition of the standard cysteine method gives a percent recovery value of I 02.07±0.09%.